INTERFERENSI LEKSIKAL BENTUK DASAR BAHASA JAWA TUBAN DALAM BAHASA INDONESIA: SUATU TINJAUAN DESKRIPTIF - Mulyani, Wahyu (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
One type of interference is interference lexical. One of the Lexical interference Types is thebasic interference lexical form. The aim of this study is to describe the basic forms of lexical interference Tubanese / Javanese language in Indonesian Language.The method used is a qualitative description. Theresults of the analysis showed that the language used in writing the synopsis, the strengths and weaknesses of the movie by the students of class XI SMAN 1 Tuban who are still experiencing interference lexical basic form. The interference occurs because of the affected Tubanese / Javanese language, bilingual students, and the student still finds it difficult in Indonesian Language Synonym.